2019
DOI: 10.1038/s41467-019-09735-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome-derived phenyl sulfate contributes to albuminuria in diabetic kidney disease

Abstract: Diabetic kidney disease is a major cause of renal failure that urgently necessitates a breakthrough in disease management. Here we show using untargeted metabolomics that levels of phenyl sulfate, a gut microbiota-derived metabolite, increase with the progression of diabetes in rats overexpressing human uremic toxin transporter SLCO4C1 in the kidney, and are decreased in rats with limited proteinuria. In experimental models of diabetes, phenyl sulfate administration induces albuminuria and podocyte damage. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 71 publications
6
183
0
Order By: Relevance
“…More than one hundred trillion microbes exist in the intestinal tract, one of the biggest immune organs of the human body [12]. An increasing number of studies have revealed that the gut-kidney axis may contribute to the pathogenesis of numerous diseases [4,5]. However, only one pilot study with a relatively small number of samples has reported the dysregulation of the gut microbiome in IgAN patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one hundred trillion microbes exist in the intestinal tract, one of the biggest immune organs of the human body [12]. An increasing number of studies have revealed that the gut-kidney axis may contribute to the pathogenesis of numerous diseases [4,5]. However, only one pilot study with a relatively small number of samples has reported the dysregulation of the gut microbiome in IgAN patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, modi cations of the gut microbiota have been recognized as a risk factor for several kidney diseases, including diabetic nephropathy, chronic kidney diseases, cardiovascular disease, in ammatory bowel disease, obesity, and several cancers [3][4][5]. Although a previous study has reported that the gut microbial community in IgAN patients is substantially changed when compared to healthy controls [6], the precise differences and the relationship between the microbes and severity of IgAN clinical manifestations are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…; Kikuchi et al . ). Phenylacetate, a microbial product of phenylalanine, has been reported to trigger steatosis (infiltration of liver cells with fat) in mice and primary cultures of human hepatocytes (Hoyles et al .…”
Section: Diet‐derived Microbial Metabolites In Health and Diseasementioning
confidence: 97%
“…Apart from SCFAs, these proteolytic degradation products have in general been considered to be deleterious for the host (Nyangale et al 2012). For example, phenolicand indolic acid-derived host-microbial co-metabolites, such as p-cresol sulphate, phenol sulphate, phenylacetylglutamine and indoxyl sulphate, have been associated with kidney diseases (Shafi et al 2015;Devlin et al 2016;Kikuchi et al 2019). Phenylacetate, a microbial product of phenylalanine, has been reported to trigger steatosis (infiltration of liver cells with fat) in mice and primary cultures of human hepatocytes (Hoyles et al 2018).…”
Section: Microbial Proteolytic Degradation Productsmentioning
confidence: 99%
“…Importantly, the levels of these colon-derived metabolites were substantially higher in the patients with ESKD than in individuals with normal kidney function, and the majority were not effectively removed by conventional hemodialysis. Abe and colleagues (36) have raised specific interest in phenyl sulfate, a tyrosine metabolite derived from gut microbes, as a potential causal factor in diabetic kidney disease. In patients with diabetes, they found that phenyl sulfate levels correlate with albuminuria, and, further, that phenyl sulfate administration and inhibition of the bacterial enzyme responsible for its synthesis induce and ameliorate albuminuria in mice, respectively.…”
Section: Metabolomics and The Contribution Of The Gut Microbiome To Umentioning
confidence: 99%